Towards Green Behavior: Egoistic And Biospheric Values Enhance Green Self-Identities - Erna Sofriana Imaningsih; Mohd Yusoff Yusliza; Hamdan Hamdan; Eri Marlapa; Aldina Shiratina (Jurnal Manajemen, 2023)
The focus of this study aims to analyze the egoistic, biospheric and green self-identity values of green purchase intentions in Indonesia who have experience consuming green brands. Because the research approach used purposive nonprobability sampling, questionnaire techniques and PLS data analysis were chosen. The results of this study show that egoistic value has a positive effect on green self-identity but negatively on green purchase intention. The value of the biosphere hurts green self-identity but positively on green purchase intention. Finally, green self-identity has a positive effect on green purchase intention. Of course, this will be an essential contribution to future research as additional knowledge, especially for governments, developers, managers or other business actors in realizing environmentally friendly behaviour. The practical and theoretical implications of this study are discussed in more depth.